Digital transformation in Cambodian higher education: Current trends and future directions - Flores, Edman; Mean, Udam (Edelweiss Applied Science and Technology, 2025)
This paper delves into stakeholder perspectives on the current state and future of digital transformation in higher education institutions (HEIs) in Cambodia. Through online surveys, data were collected from academic staff, management, support personnel, and students across both private and public HEIs. The findings reveal generally positive assessments of the extent and effectiveness of digital transformations in Cambodian higher education. Respondents expressed a collective aspiration for enhanced digital infrastructure, training, and leadership support, while also highlighting persistent disparities in access and digital competence among students. The study underscores the need for a coherent, socially responsive digital strategy that addresses Cambodia’s unique socio-economic factors. Participants recognize the transformative potential of technologies such as AI, gamification, and blended learning in enhancing educational experiences. However, concerns regarding equity must be prioritized to prevent exacerbating existing divides. The findings emphasize the importance of ongoing stakeholder collaboration and strategic leadership from governmental and educational authorities to foster a comprehensive digital ecosystem that promotes equitable access to education. Ultimately, this research offers critical insights for policy-making, institutional planning, and educational practices. It advocates for a balanced approach between technological integration and maintaining essential human elements in learning environments. Further research is recommended to capture a wider range of voices and experiences from diverse educational contexts within Cambodia, enabling a more nuanced understanding of the challenges and prospects of digital transformation in higher education.